2021
DOI: 10.3390/biom11010103
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Gallus Epidermal Growth Factor (gEGF) with Food-Grade Lactococcus lactis Expression System and Its Biological Effects on Broiler Chickens

Abstract: As a multifunctional polypeptide, epidermal growth factor (EGF) increases growth performance or enhances resistance to diseases in commercial broilers under adverse conditions. In this study, a recombinant Lactococcus lactis was established to produce the secretory form of bioactive gEGF. The results of in vitro testing showed that gEGF promoted the proliferation of chicken embryo fibroblast cells. A total of 63 5-day-old broiler chickens were evenly divided into three groups and treated with either M17 medium… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…As shown in Figure 2 D, the LMH cell proliferation was significantly enhanced by the treatment of rEGF-EtMIC7 with a concentration of 0.1 µg/mL. The results showed that EGF-EtMIC7 is similar to chicken EGF, because both can promote the proliferation of the chicken cell lines ( Zhou et al, 2021 ). In addition, Akt activation was reported to affect cell proliferation ( Wee and Wang, 2017 ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…As shown in Figure 2 D, the LMH cell proliferation was significantly enhanced by the treatment of rEGF-EtMIC7 with a concentration of 0.1 µg/mL. The results showed that EGF-EtMIC7 is similar to chicken EGF, because both can promote the proliferation of the chicken cell lines ( Zhou et al, 2021 ). In addition, Akt activation was reported to affect cell proliferation ( Wee and Wang, 2017 ).…”
Section: Resultsmentioning
confidence: 87%
“…The effects of rEGF-EtMIC7 on the proliferation of LMH cells were examined with Cell Counting Kit-8 ( CCK-8 ) assay ( Zhou et al, 2021 ). Briefly, LMH cells were cultured in DMEM with 10% FBS for 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Lactobacillus was proven to produce lactic acid, thereby decreasing the pH value of the intestinal tract, which was consistent with the results of the current study (Sha et al, 2016). There were several reports indicating that dietary supplementation of Lactobacillus improved the host gut health, feed utilization, growth, immune status and survival (Gajbhiye & Kapadnis, 2021; Lebeer et al, 2008; Parma et al, 2020; Zhou et al, 2021). Higher abundances of potentially pathogenic bacteria such as Pseudomonas , Escherichia‐Shigella , Mycoplasma , Acinetobacter , Vibrio and Sneathia were detected in the SG group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hu et al [44] reported the production of fibroblast EGF using an IPTG-inducible promoter in B. subtilis, with a yield of 31 mg/L. Although a nisin-inducible expression system in Lactococcus lactis could reach a productivity of 2.67 mg/L [45], it requires the addition of 10 ng/mL nisin to induce human EGF (hEGF) production.…”
Section: Introductionmentioning
confidence: 99%